Modeling computational fluid dynamics of multiphase flows in elbow and T-junction of the main gas pipeline - Doroshenko, Yaroslav; Doroshenko, Julia; Zapukhliak, Vasyl; Poberezhny, Lyubomyr; Maruschak, Pavlo (Transport, 2019)
The research was performed in order to obtain the physical picture of the movement of condensed droplets and solid particles in the flow of natural gas in elbows and T-junctions of the linear part of the main gas pipeline. 3D modeling of the elbow and T-junction was performed in the linear part of the gas main, in particular, in places where a complex movement of multiphase flows occurs and changes its direction. In these places also occur swirls, collisions of discrete phases in the pipeline wall, and erosive wear of the pipe wall. Based on Lagrangian approach (Discrete Phase Model – DPM), methods of computer modeling were developed to simulate multiphase flow movement in the elbow and T-junction of the linear part of the gas main using software package ANSYS Fluent R17.0 Academic. The mathematical model is based on solving the Navier–Stokes equations, and the equations of continuity and discrete phase movement closed with Launder–Sharma (k–e) two-parameter turbulence model with appropriate initial and boundary conditions. In T-junction, we simulated gas movement in the run-pipe, and the passage of the part of flow into the branch. The simulation results were visualized in postprocessor ANSYS Fluent R17.0 Academic and ANSYS CFD-Post R17.0 Academic by building trajectories of the motion of condensed droplets and solid particles in the elbow and T-junction of the linear part of the gas main in the flow of natural gas. The trajectories were painted in colors that match the velocity and diameter of droplets and particles according to the scale of values. After studying the trajectories of discrete phases, the locations of their heavy collision with the pipeline walls were found, as well as the places of turbulence of condensed droplets and solid particles. The velocity of liquid and solid particles was determined, and the impact angles, diameters of condensed droplets and solid particles in the place of collision were found. Such results provide possibilities for a full and comprehensive investigation of erosive wear of the elbow and T-junction of the linear part of the gas main and adjacent sections of the pipeline, and for the assessment of their strength and residual life.